The Sustainable Development Goals and the systems approach to sustainability - Edward Barbier; Joanne C. Burgess (Kiel Institute for the World Economy (IfW), 2017)
The authors explore the link between the systems approach to sustainability and the 17 Sustainable Development Goals (SDGs), which were formally adopted by the UN in 2015. The systems approach depicts sustainable development as the intersection of the goals attributed to three interlinked systems: environmental (or ecological), economic and social. The authors illustrate how each of the 17 SDGs can be characterized as a goal primarily attributed either to the environmental, economic or social system, and as suggested by the systems approach, there may be important tradeoffs in attempting to attain all these goals simultaneously. By adopting standard methods of the theory of choice and welfare under imposed quantities, the authors show that is possible to measure the welfare effects of an increase in the indicator level for one SDG by identifying the tradeoffs that occur with achieving another goal. They present a quantitative assessment of current progress and tradeoffs among the 17 SDGs, using a representative indicator for each goal. They then conduct a preliminary welfare analysis of these tradeoffs through employing the approach developed in this paper. Although this analysis focuses on the potential tradeoffs among SDGs, the approach could also be applied to show complementarities, or "winwins", in simultaneous progress among two or more SDGs. Such an analysis can help in the design of appropriate policy interventions to achieve specific SDGs, minimizing the potentially negative knock-on effects on some goals whilst capitalizing on the positive win-win impacts on other SDGs.
Keywords: Q01; O20; D61; Q56; 330; sustainable development; Sustainable Development Goals; systems approach; tradeoffs; United Nations